THE EFFECT OF IMPROVE METHOD ON MATEMATICAL UNDERSTANDING ABLILITY AND SELF-DEVELOPMENT - Handayani, Rika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Mathematical concepts must not only be understood or memorized in order for students to learn them effectively. Learners will more easily achieve learning objectives if they have a strong ability to understand mathematical concepts. However, in reality, researchers found that there are still many students who have difficulty in understanding the mathematical concepts taught by teachers during their education. This hampers the learning process because it causes the teacher to have to repeat the material continuously. The research method used was a pseudo-experiment with a 2x2 factorial design with level-based treatment. The data analysis technique used two-way ANOVA. The results of this study are as follows: 1) Overall mathematical understanding ability of students taught with IMPROVE method is higher than students taught with conventional method; 2) There is an interaction between learning method and PAM on mathematical understanding ability; 3) For students with high PAM, the mathematical comprehension ability of students taught with IMPROVE method is higher than that of students taught with conventional method; 4) For students with low PAM, the mathematical comprehension ability of students taught with IMPROVE method is higher than that of students taught with conventional method. For students with low PAM, the mathematical comprehension ability of students taught with IMPROVE method is lower than students taught with conventional method; 5) Self-development of students taught with IMPROVE learning method is higher than students taught with conventional method.